Betaine Reduces Serum Uric Acid Levels and Improves Kidney Function in Hyperuricemic Mice - Liu, Yang-Liu; Pan, Ying; Wang, Xing; Fan, Chen-Yu; Zhu, Qin; Li, Jian-Mei; Wang, Shui-Juan; Kong, Ling-Dong (Planta Medica, 2013)
Betaine as a dietary alkaloid has attracted the attention of patients with kidney diseases. This study aimed to investigate the effects of betaine on serum uric acid levels and kidney function, and explore their underlying mechanisms in potassium oxonate-induced hyperuricemic mice. Betaine at 5, 10, 20, and 40 mg/kg was orally administered to hyperuricemic mice for 7 days and found to significantly reduce serum uric acid levels and increase fractional excretion of uric acid in hyperuricemic mice in a dose-dependent manner. It effectively restored renal protein level alterations of urate transport-related molecular proteins urate transporter 1, glucose transporter 9, organic anion transporter 1, and ATP-binding cassette subfamily G member 2 in this model, possibly resulting in the enhancement of kidney urate excretion. Moreover, betaine reduced serum creatinine and blood urea nitrogen levels and affected urinary levels of beta-2-microglobulin and N-acetyl-beta-D-glucosaminidase as well as upregulated renal protein levels of organic cation/carnitine transporters OCT1, OCTN1, and OCTN2, resulting in kidney function improvement in hyperuricemic mice. The findings from this study provide evidence that betaine has anti-hyperuricemic and nephroprotective actions by regulating protein levels of these renal organic ion transporters in hyperuricemic mice.
Keywords: betaine; hyperuricemic mice; renal function; renal organic ion transporters